Effect of layer and stacking sequence in simultaneously grown 2H and 3R WS2 atomic layers. (3rd June 2019) - Yang, Ruilong; Feng, Shanghuai; Lei, Xunyong; Mao, Xiaoyu; Nie, Anmin; Wang, Bochong; Luo, Kun; Xiang, Jianyong; Wen, Fusheng; Mu, Congpu; Zhao, Zhisheng; Xu, Bo; et al.
Abstract: In two-dimensional layered materials, layer number and stacking order have strong effects on the optical and electronic properties. Tungsten disulfide (WS2 ) crystal, as one important member among transition metal dichalcogenides, has been usually prepared in a layered 2H prototype structure with space group P 63 /mmc ( D 6 h 4 ) in spite of many other expected ones such as 3R. Here, we report simultaneous growth of 2H and 3R stacked multilayer (ML) WS2 crystals in large scale by chemical vapor deposition and effects of layer number and stacking order on optical and electronic properties. As revealed in Raman and photoluminescence (PL) measurements, with an increase in layer number, 2H and 3R stacked ML WS2 crystals show similar variation of PL and Raman peaks in position and intensity. Compared to 2H stacked ML WS2, however, 3R stacked one always exhibits the larger red (blue) shift of Raman E 2 g 1 (A1g ) peak and the appearance of PL A, B and I peaks at lower energies. Thereby, PL and Raman features depend on not only layer number but also stacking order. In addition, circularly polarized luminescence from two prototype WS2 crystals under circularly polarized excitation has also been investigated, showing obvious spin or valley polarization of these CVD-grown multilayer WS2 crystals.